log3log8log2 (x-5) = log3 2-1

0 голосов
77 просмотров

log3log8log2 (x-5) = log3 2-1


Алгебра (12 баллов) | 77 просмотров
Дан 1 ответ
0 голосов

Log3log8log2 (x-5) = log3(2) -1
log3log8log2 (x-5) = log3(2) - log3(3)
 log3log8log2 (x-5) = log3(2/3)
  log8log2 (x-5) = 2/3
  log8log2 (x-5) = log8 (8^(2/3))
  log8log2 (x-5) = log8(4)
   log2 (x-5) = 4
   log2 (x-5) = log2(2^4)
    log2 (x-5) = log2(16)
   x-5 =16
    x=21  
Проверка
 log3log8log2 (21-5) =  log3log8log2(16) =  log3log8(4) = log3(2/3)  = log3(2)-1
Ответ:21 

(11.0k баллов)